Dynamic changes in the body composition during chemotherapy for gastrointestinal tumors in the context of active nutrition intervention - Xu, Ting; Li, Zhenhao; Li, Hui; Hou, Jixiang; Li, Jingjing; Jin, Gaowa; Li, Shaohua; Li, Quanfu (Frontiers in Oncology, 2022)
Objective To explore the dynamic changes in the body composition during chemotherapy in patients with gastrointestinal malignancies in the context of active nutrition intervention. Methods Patients with gastrointestinal malignancies receiving first-line chemotherapy in the Department of Medical Oncology of Ordos Central Hospital from September 2019 to January 2022 were included in this study. The Nutritional Risk Screening form 2002, Patient-Generated Subjective Global Assessment form, bioelectrical impedance analysis, and dynamic changes in L3 skeletal muscle index (SMI) (L3SMI) were assessed at baseline and after chemotherapy. The recommended protocol of the Nutrition Guidelines for Cancer Patients in China 2020 was adopted as the active nutrition intervention. Chemotherapy-related toxic adverse reactions and the degree of toxicity were recorded with the adoption of the Common Terminology Criteria for Adverse Events version 4.0 by the National Institutes of Health. The type of toxicity Chemotherapy-Induced Nauseaand Vomiting(CINV) and hematological. Results Fifty cases were enrolled in the study, and 38 cases completed the dynamic follow-ups. The average follow-up time was 125.63 d. In the context of active nutrition intervention, the prevalence of sarcopenia decreased from 26.3% before chemotherapy to 21.1% after chemotherapy. The average L3SMI decreased from 38.77 cm2/m2 to 38.04 cm2/m2, with a reduction of 1.41% ± 8.49% (P = 0.177). The SMI remained stable or increased in 57.9% (22/38) of patients. The benefit of active nutrition intervention was greater in the sarcopenic group than in the non-sarcopenic group (P = 0.033). There was an increased incidence of chemotherapy-related toxic adverse reactions of ≥ grade 3 during chemotherapy in the sarcopenic group compared with the muscle retention/gain group (P = 0.089). Conclusion Active nutrition intervention might decrease the degree of reduction of L3SMI and the incidence of sarcopenia in patients with gastrointestinal tumors and raise the proportion of patients with stable or increased SMI during chemotherapy.